2015
DOI: 10.4236/as.2015.62024
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical Properties of Sesame (<i>Sesamum indicum</i> L.) Varieties Grown in Northern Area, Ethiopia

Abstract: This study was conducted to evaluate the physico-chemical properties of three sesame varieties: Adi, Bawnji and T-85. Sesame varieties showed significant (p ≤ 0.05) differences on some physical properties, proximate, mineral, anti-nutritional (phytic acid) and antioxidant compositions. The average values of 1000 seed weight were ranged from (2.74 -3.16 g) and true density from (1190.66 to 1215.58 kg m −3 ). The moisture (wb), crude protein, ash, fat, fiber, total carbohydrate, Ca, Zn and Fe (db) were ranged: 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
5
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 33 publications
4
16
5
2
Order By: Relevance
“…As it can be seen from Table 5, the levels of essential and non-essential metals determined in the sesame seed samples of this work are either lower than the reported data or in good agreement with other studies obtained in the same and other countries. Thus, the amount of Fe recorded in this study was lower than the concentrations of iron reported by Zebib et al [41] (102-108 mg/L), Özcan et al [43] (63.3-254 mg/L) and Obiajunwa et al [42] (113 mg/L). Zinc is present in appreciable amount in the ranges of 57.9-67.…”
Section: Comparison Of the Mean Levels Of Studied Metals With Literatcontrasting
confidence: 81%
“…As it can be seen from Table 5, the levels of essential and non-essential metals determined in the sesame seed samples of this work are either lower than the reported data or in good agreement with other studies obtained in the same and other countries. Thus, the amount of Fe recorded in this study was lower than the concentrations of iron reported by Zebib et al [41] (102-108 mg/L), Özcan et al [43] (63.3-254 mg/L) and Obiajunwa et al [42] (113 mg/L). Zinc is present in appreciable amount in the ranges of 57.9-67.…”
Section: Comparison Of the Mean Levels Of Studied Metals With Literatcontrasting
confidence: 81%
“…The values obtained for the mass of 1000 seeds are close to those found by Zebib et al (2015) and Ozkan et al (2012), who have found values for different cultivars ranging from 2.7 to 3.1 and from 2.7 to 3.9, respectively. However, the values found are lower than those found by Queiroga et al (2012), who found a minimum 3.0 g value for the mass of 1000 seeds for the BRS Silk cultivar.…”
Section: Resultssupporting
confidence: 89%
“…From the nutritional profile, sesame is categorized among nutraceutical and functional foods. As [3] reported the physico-chemical properties of three sesame varieties grown in Northern area of Ethiopia. Results showed that Ethiopian sesame varieties were good source in nutrients and were functional foods for human nutrition and utilization.…”
Section: Introductionmentioning
confidence: 99%